Assessment of the sediment quality along Darau river estuary Kota Kinabalu Sabah - Muhammad Rashid Abdul Rahim (2014)
This research was conducted to observe the distribution of particle sizes, the concentration of nutrients, such as Total Organic Carbon (%), Total Inorganic Carbon (%), Total Phosphorus (mg of P/100g) and Total Nitrogen (%) and heavy metal concentration in sediment along the Darau river estuary. Six stations were selected and located near the source of nutrients. The six stations started with the upper stream of the estuary, the construction site, Ko-Nelayan shrimp farm, housing area, mixing point between Darau and Ukas River and control station that located 1.5 kilometers from the river estuary. Along the Darau river estuary, the dominant type of sediment particles is silt (61.31%), followed by sand (37.42%) and mud (1.27%). Total Organic Carbon in sediment was range from 0.11%-3.33%, while the Total Inorganic Carbon (0.16%-4.52%), Total Phosphorus (0.22 mg of P/100g - 0.77 mg of P/100g) and Total Nitrogen (0.01%-0.18%). The significant different was observed between the sediment nutrients with Total Organic Carbon and Total Inorganic Carbon (F=3.141, P<0.05), Total Nitrogen (F=24.03, P<0.05) and Total Phosphorus (F=13.03, P<0.05) within stations. In conclusion, the sediment from Darau river estuary is mainly comprised of silt. While the nutrient content differs among the stations and related to the sources of origin along the river estuary. The highest percentage of heavy metal element along Darau River estuary is Iron (Fe)with (365.31 ppm) and lowest percentage was Arsenic (As) with (0.12 ppm). The sequence of heavy metal elements are as follow; Iron (Fe) > Aluminium (Al) > Magnesium (Mg) > Mangane (Mn) > Zinc (Zn) > Lead (Pb) > Nickel (Ni) > Copper (Cu) > Chromium (Cr) >Arsenic (As).